Kemampuan Informatika Perawat Sebagai Modal Penerapan Pencatatan Keperawatan Elektronik di Rumah Sakit - Stephanie Dwi Guna; Yureya Nita (Jurnal Keperawatan Muhammadiyah, 2021)
The implementation of Information Technology in nursing improves the quality of care. Electronic nursing record is an innovation that enhances the efficiency of nursing care. The informatics skill is needed for nurses to adapt with the innovation of Information Technology. This paper aims to discuss the informatics skill of nurses at one public hospital in Pekanbaru, Riau, Indonesia. This study was analytical study with cross sectional approach. This study involved 237 nurses and used purposive sampling technique. The data was being taken by using self- assessed nursing informatics skill/ NICAT questionnaire which divides the informatics skill in to beginner, advance beginner, competent, proficient and expert. The result of the study showed that the majority of nurses’ informatics skill was competent (49.4%) and only 4.6% that is expert. Informatics skill of the nurses related to the sex, education level and length of work. The informatics training will help nurses to improve their informatics skill.